Quantifying loss and damage from compound climate risk - Engdaw, Mastawesha Misganaw; Ghosh, Aniruddha; Chilambe, Pedro Anglaze; Ramirez Villegas, Julian; Girvetz, Evan; Steiner, Andrea K. (2025)
Recent analyses of multi-hazard attribution studies reveal that compound climate extremes often lead to disproportionately high levels of loss and damage. However, significant losses from single extreme events—sometimes exceeding those from compound events—cannot be overlooked. This highlights a critical limitation: traditional univariate analyses of extremes may underestimate the full extent of loss and damage. This Working Paper emphasizes the need for comprehensive risk assessments to improve the estimation of loss and damage and to strengthen the effectiveness of interventions. To support this, we introduce a novel, time-sensitive, modeling-based conceptual framework that distinguishes between avoided and unavoidable loss and damage. This framework also enables the evaluation of how coordinated interventions contribute to increasing the share of avoidable loss and damage. These roles of the framework and their effectiveness will enhance with further development of impact models. By integrating comprehensive risk analysis with this new framework, it becomes possible to more rigorously identify and assess loss and damage that might otherwise be underestimated. Furthermore, the approach proposed here contributes to promoting greater equity in decision-making processes related to the Loss and Damage Fund. Whenever possible, averting and minimizing loss and damage remains the most effective strategy. To this end, aiming to enhancing the effectiveness and efficiency of interventions that increase avoidable loss and damage, we suggest several policy recommendations: diversifying assessment to economic sectors such as livestock for addressing loss and damage of pastoral communities, minimizing trade-offs though harmonized interventions, accelerated project approval procedure, and data access and sharing.